2017
DOI: 10.1016/j.bioactmat.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitin-PLA laminated composite for implantable application

Abstract: The present study explores the possibilities of using locally available inexpensive waste prawn shell derived chitin reinforced and bioabsorbable polylactic acid (PLA) laminated composites to develop new materials with excellent mechanical and thermal properties for implantable application such as in bone or dental implant. Chitin at different concentration (1–20% of PLA) reinforced PLA films (CTP) were fabricated by solvent casting process and laminated chitin-PLA composites (LCTP) were prepared by laminating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
76
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 27 publications
16
76
1
2
Order By: Relevance
“…The elastic modulus value showed that the stiffness of the PLA was enhanced with the addition of chitin and reduced starch content. The stiffness of the composite could be attributed to the combined effect of the brittleness of starch and the enhanced toughness of chitin [22,31]. The values of the elastic modulus corroborated the possible use of the material for the repair of cancellous bone.…”
Section: Tensile Propertiesmentioning
confidence: 56%
See 2 more Smart Citations
“…The elastic modulus value showed that the stiffness of the PLA was enhanced with the addition of chitin and reduced starch content. The stiffness of the composite could be attributed to the combined effect of the brittleness of starch and the enhanced toughness of chitin [22,31]. The values of the elastic modulus corroborated the possible use of the material for the repair of cancellous bone.…”
Section: Tensile Propertiesmentioning
confidence: 56%
“…The shift indicated that the addition of chitin and starch particles exerted a considerable effect on the crystalline properties of PLA. An increase in the starch or chitin blend caused a slight noticeable improvement in the crystallinity of the neat PLA [22,39]. A small improvement was noticed with an increase in starch content, as shown in the degree of crystallinity (DOC) of sample A5 (PLA/2% C/6% S).…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength is seen to reduce with an increase in starch content and decrease chitin content. This is an indication of the miscibility of the three polymer blends [12,24]. Also, the increase in tensile strength is between 59% to 85%.…”
Section: Tensile Propertiesmentioning
confidence: 88%
“…This miscibility of the polymer composite can be attributed to the use of chloroform as the plasticizer and the interfacial bonding of PLA/chitin and chitin /starch. Chitin has been reported to act as a compatibilizer between PLA and starch [12,24,25,29,30]. The images are characterized with network flakes of starch-chitin blends and edges with no voids.…”
Section: Impact and Morphological Propertiesmentioning
confidence: 99%